KEHIDUPAN WAJAR DAN PERBAHASANNYA DALAM ISLAM: SATU KAJIAN AWAL: DECENT LIVING AND ITS DISCUSSIONS IN ISLAM: A PRELIMINARY STUDY - binti Abdul Jalil, Nur Syahidah; Mohamad, Muhammad Hisyam; binti Majid, Wan Roslili (Online Journal of Islamic Management and Finance (OJIMF), 2022)
In general, human beings require various needs that could enable them to lead a comfortable life in this world. In this regard, the needs of Muslims are different from those of the common ones as the Islamic worldview of life encompasses the worldly as well as the hereafter. As such, the element of income is not an absolute determinant of a decent life from an Islamic perspective. Based on the content analysis of documents published by five competent authorities and additional views of three experts interviewed, this study suggests six elements to enable a Muslim individual to live a decent life in this world, namely income, protection, family institutions, interaction space, financial inclusion; and spiritual capacity and recreation. This study, however, does not suggest a quantitative value to the proposed elements. Thus, if there was a quantitative value that could serve as an indicative benchmark for a decent standard of living as a whole, it certainly could create more space for research to improve the standard of living of human beings.